(untitled) (Research, Society and Development, 2020)
The objective of the research was to evaluate the physiological performance of soybean seeds treated with mycorrhizal inoculant based on Rhizophagus intraradices, (20,800 propagules / g.) And their interaction with fungicide (Metalaxil-M 2% w / v; Tiabendazole 15% w / ve Fludioxonil 2.5% w / v). The experiment was carried out at the Federal Technological University of Paraná, in the year 2019. Two batches of soybean seeds of the cultivar M 5838 IPRO were used, one batch with low vigor (Vigor 74% and germination 87%) and another with high vigor (Vigor 92% and germination 92%). The variables used were Germination; Seedling vigor classification; Seedling length; Dry mass; Accelerated aging; Field emergency and Average emergency time. The test was carried out in a completely randomized design (DIC), with four replications. It was concluded that, in relation to vigor, the high vigor lot obtained better performance in relation to the physiological parameters of the seeds and presented little or no interference from the evaluated treatments. In the low vigor lot, treatments with mycorrhizal Rhizophagus intraradices and or the association with fungicide, demonstrated a certain specificity regarding the interference in the physiological parameters in soybean seeds, and the germination, vigor and dry matter variables improved with joint use. Fungicide and mycorrhiza. Studies on the efficiency of these treatments need to be validated in the field regarding the improvement of the agronomic and productive parameters of the soybean crop.